Organizational Theory and Public Policy - richard h. hall (Sage Publication, 1983)
Organizations both make and implement policy, and policy is most often directed at organizations. Yet the complex interaction between policy and organization is not often studied. The essays in this volume apply the insights of organization studies to the study of policy. They also deal with political and economic issues that are often passed over by organization studies. The contributors discuss the increasing political influence of large corporations, the limits to rationality in regulation, policy for specific issues such as care for the elderly, and issues of organization theory. Each essay considers the contributions that policy and organization studies can make to these issues.